How do firms respond to reduced private equity buyout activity? - LO, Yi-hsin (Institutional Knowledge at Singapore Management University, 2022)
This paper presents new evidence on the economic role of private equity buyouts by exploiting the staggered adoption of the constructive fraud provision by U.S. state courts. The law unintentionally shifts the credit default risk borne by existing unsecured creditors of the buyout target to the selling shareholders and lenders in the form of ex-post litigation risk, thereby discouraging buyout activity. Using a difference-in-differences framework, I find that firms raise less capital, reduce payouts and investments, and form alliances with employees. Firms also avoid positive NPV projects that carry too much risk. These findings are consistent with managers enjoying a quiet life. Further analysis indicates that this behavior of managers adversely affects creditors.